OMEGA-3 FATTY ACIDS AND RHEUMATOID ARTHRITIS: MECHANISMS AND CLINICAL EVIDENCE - Adrianna Ewa Pękacka,; Julia Borkowska,; Julia Skowrońska-Borsuk,; Martyna Narożniak,; Bartłomiej Czerwiec,; Adam Borsuk,; Joanna Katarzyna Pergoł,; Malwina Wojtas,; Zuzanna Krupa,; Julia Sposób, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint inflammation and systemic manifestations. Omega-3 fatty acids, particularly EPA and DHA, have been suggested to modulate inflammatory processes and immune responses. This review aims to summarize current evidence on the role of omega-3 fatty acids in the pathophysiology and clinical management of RA.Material and Methods: A literature search was conducted using PubMed to identify original studies, randomized controlled trials, meta-analyses, and reviews examining the effects of omega-3 supplementation on RA. Key outcomes included disease activity, inflammatory markers, pain, morning stiffness, and use of nonsteroidal anti-inflammatory drugs.Results and Conclusion: Omega-3 fatty acids demonstrate anti-inflammatory properties through modulation of cytokine production, competition with omega-6 fatty acids in eicosanoid pathways, and generation of pro-resolving lipid mediators. Clinical studies indicate that supplementation may reduce morning stiffness, pain, and NSAID requirements in RA patients, although heterogeneity in doses, sources, and study duration limits generalizability. Omega-3 fatty acids represent a promising adjunctive therapy for RA, but further standardized clinical trials are warranted.